Tìm x biết rằng:
a) 45x : 5x = 81 b) 7(x + 1)(2x – 3) = 1
c) 4x+1 – 22x = 192 d) x3 – 4x = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(C=-\left(\frac{3}{7}+\frac{3}{8}\right)-\left(-\frac{3}{8}+\frac{4}{7}\right).\)
\(C=-\frac{45}{56}-\frac{11}{56}\)
\(C=-1\)
\(C=-\left(\frac{3}{7}+\frac{3}{8}\right)-\left(-\frac{3}{8}+\frac{4}{7}\right)\)
\(C=-\frac{3}{7}-\frac{3}{8}+\frac{3}{8}-\frac{4}{7}\)
\(C=-\frac{3}{7}-\frac{4}{7}\)
\(C=-\frac{7}{7}=-1\)
F = x4 - 2x2 + 3 = x4 - 2x2 + 1 + 2 = (x2 - 1)2 + 2 \(\ge2\)
=> Min F = 2
Dấu "=" xảy ra <=> x2 - 1 = 0
<=> x = \(\pm1\)
Vậy Min F = 2 <=> x = \(\pm1\)
Ta có G = (x2 + 2)2 - 3
= x4 + 4x2 + 1 = x2(x2 + 4) + 1 \(\ge1\)
=> Min G = 1
Dấu "=" xảy ra <=> x2(x2 + 4) = 0
<=> x = 0
Vậy Min G = 1 <=> x = 0
a) 45x : 5x = 81
=> ( 45 : 5 )x = 81
=> 9x = 92
=> x = 2
a) 45x : 5x = 81 <=> (45 : 5)x = 81 <=> 9x = 92 => x = 2
b) 7(x + 1)(2x - 3) = 1
<=> 7(x + 1)(2x - 3) = 70
=> (x + 1)(2x - 3) = 0
<=> \(\orbr{\begin{cases}x+1=0\\2x-3=0\end{cases}}\)<=> \(\orbr{\begin{cases}x=-1\\x=\frac{3}{2}\end{cases}}\)
c) 4x+1 - 22x = 192
<=> 4x.4 - 4x = 192
<=> 4x . 3 = 192
<=> 4x = 64
<=> 4x = 43 => x = 3
d) x3 - 4x = 0
<=> x(x2 - 4)) = 0
<=> \(\orbr{\begin{cases}x=0\\x^2-4=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=0\\x=\pm2\end{cases}}\)